Eco-Literacy: Living Pharmacy and Eco-Enzyme Practices at SMPN 30 Bulukumba - Hidayah, Ummul; Amir, Nuragni Sakinah; Mukarramah,; Amalia, Miftahul; Basir, A. Mega Lutfiah; Mar'atushaliha, Salsa; Tamrin, A. Nurzakiyah; Hamsa, Syamsul; Syahriani, (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2025)
Bulukumba Regency is one of the administrative districts in South Sulawesi. The aim of this research is to increase students' ecological awareness by introducing the concept of a living pharmacy which emphasizes maintaining plants that are beneficial for health, the environment and the use of empty land and to introduce and inform about the processing of unused organic waste into liquid fertilizer that is beneficial for plants (Ecoenzyme). This research also aims to measure the effectiveness of using ecoenzymes in increasing plant productivity. In this research, testing and analysis methods were used for natural enzymes produced from organic materials and methods for identifying medicinal plants.